Alkene synthesis using phosphonium ylides as umpolung reagents - Vu, Minh Duy (2020)
We report a transformation between a well‐known nucleophile, phosphonium ylide, and an electrophile. Subsequent ylide‐ylide coupling achieves unusual (Z )‐selectivity as compared to the conventional Wittig olefination. The synthesis of medium‐sized ring olefins has also been demonstrated, together with a one‐pot olefination from activated halides.